488 REST-ON: Efficacy of FT218 for Daytime Sleepiness, Sleep Quality, Hallucinations, and Sleep Paralysis in Patients With Narcolepsy. (3rd May 2021) - Thorpy, Michael; Roth, Thomas; Dauvilliers, Yves; Kushida, Clete; Shapiro, Colin; Corser, Bruce; Ajayi, Akinyemi; Dubow, Jordan; Seiden, David; Rosenberg, Russell
Abstract: Introduction: Sodium oxybate (SO) is an effective treatment for narcolepsy; however, currently available formulations must be taken twice nightly. FT218 is an investigational once-nightly controlled-release formulation of SO. Here, we evaluated the efficacy of FT218 on excessive daytime sleepiness (EDS), self-reported sleep quality/refreshing nature of sleep, sleep paralysis (SP), and hypnagogic hallucinations (HH) in patients with narcolepsy. Methods: In this phase 3, randomized, double-blind, placebo-controlled, multicenter study, patients aged ≥16 years with narcolepsy type 1 or 2 were randomized 1:1 to receive FT218 or matching placebo: 4.5 g/night (1 week), 6.0 g/night (2 weeks), 7.5 g/night (5 weeks), and 9.0 g/night (5 weeks). Secondary efficacy endpoints included EDS using the Epworth Sleepiness Scale (ESS), sleep quality/refreshing nature of sleep using a visual analog scale (VAS), and SP and HH using a sleep symptom diary. Results: A total of 212 patients were randomized and received study medication (FT218, n=107; placebo, n=105). Patients receiving FT218 had significant improvement vs placebo in EDS on the ESS: LS mean difference on ESS score between FT218 and placebo was −3.86 for 9.0 g (week 13), −3.16 for 7.5 g (week 8), and −2.06 for 6.0 g (week 3) (all P<0.001). Sleep quality/refreshing nature of sleep on VAS was also significantly improved with FT218 vs placebo (P<0.001 for all doses). Patients receiving FT218 reported less SP vs placebo (P<0.05 at all doses). Baseline values for HH were low in both treatment groups; HH was similar for both treatment groups at all study visits. The most common adverse reactions were nausea, dizziness, enuresis, headache, decreased appetite, and vomiting. Conclusion: At all evaluated doses, treatment with FT218 significantly improved EDS, sleep quality/refreshing nature of sleep, and SP vs placebo. FT218 was generally well tolerated; the most common adverse events were consistent with known SO side effects. Support (if any): Avadel Pharmaceuticals.